Pony - Palacio, R. J. (Alfred A. Knopf, 2021)
Twelve-year-old Silas is left scared and shaken by himself after three mysterious horsemen take his father away in the night. Left with no companionship except that of Mittenwool, a ghost, and a strange pony who shows up at his door uninvited, Silas mounts up and sets out on a journey across the Western American landscape to find his father and help him make sense of the mysteries of the past, future, and the changing world around him.